2019
DOI: 10.17219/acem/109976
|View full text |Cite
|
Sign up to set email alerts
|

Dietary support in insulin resistance: An overview of current scientific reports

Abstract: Over the past 30 years, a significant increase in the prevalence of insulin resistance (IR) has been observed. It is associated with more frequent occurrence of impaired glucose tolerance, diabetes, excessive weight, cardiovascular diseases, and endocrine disorders. The results of current studies do not indicate a necessity to exclude dairy products from the diet of insulin-resistant individuals. In addition, it has been found that moderate amounts of alcohol as part of a balanced, low-energy diet do not have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 54 publications
0
32
1
Order By: Relevance
“…Unbalanced diets rich in SFA lead to health problems such as increased risk of cardiovascular diseases (CVD), or insulin resistance (IR) in all individuals, general and celiac population [ 49 , 50 , 51 ]. In fact, it has been observed that people with CD show higher risk of death from CVD [ 52 ].…”
Section: Gfd In CD Treatmentmentioning
confidence: 99%
“…Unbalanced diets rich in SFA lead to health problems such as increased risk of cardiovascular diseases (CVD), or insulin resistance (IR) in all individuals, general and celiac population [ 49 , 50 , 51 ]. In fact, it has been observed that people with CD show higher risk of death from CVD [ 52 ].…”
Section: Gfd In CD Treatmentmentioning
confidence: 99%
“…is related to lower insulin sensitivity of the body tissues composed of insulin-dependent cells, such as skeletal muscle and adipocytes. The insulin plays a crucial role in glucose entry into cells, and any disturbance in insulin signal sociated with hyperglycemia This disorder that has been shown to be correlated to stress and overstimulation of the sympathetic nervous system is strongly linked to inflammation states [1] that occur due to metabolic disturbances involving glucose intolerance, leptin resistance, dyslipidemias, mitochondrial dysfunction, an increase in pro inflammatory mediators, and oxidative stress [9,11]. It can also be explained by the creation of advanced glycation end products (AGEs) due to chronic hyperglycemia.…”
Section: Insulin Resistance: General Aspectsmentioning
confidence: 99%
“…Insulin resistance (IR) is a consequence of abnormal functioning and signaling of insulin receptors, an excessively high level of insulinbinding antibodies, or an abnormal insulin molecule structure [1]. This condition manifests impaired insulin action in all insulin target organs and tissues as skeletal muscle, cardiac muscle, liver, adipose tissue, the brain as well as the vasculature [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside cardiovascular disease, its prevalence increases with an epidemic scale, as a result of an ongoing epidemiological transition in populations lifestyle inherent in globalization [19] [20] [21]. Furthermore, the results of various studies suggest a link between diet and insulin resistance both in humans [22] [23] [24] [25] [26] and in laboratory animals [27] [28] [29]. The link between diet and CVDs could be explained, at least World Journal of Cardiovascular Diseases in part, by an association between diet pattern and IR.…”
Section: Introductionmentioning
confidence: 99%